Intra-Seasonal Acoustic Variation in Humpback Whale Songs in the North Colombian Pacific - Juliana López-Marulanda; Hector Fabio Rivera-Gutierrez (Journal of Marine Science and Engineering, 2025)
Humpback whales (Megaptera novaeangliae) are well known for their complex acoustic communication, which plays a critical role in social interactions and reproduction. Understanding the variability in humpback whale songs is crucial to deciphering their communication strategies and the factors that influence these changes, which may affect reproductive success and population dynamics. While most studies of humpback whale song behavior have focused on annual variation, intra-seasonal changes remain underexplored. This study investigates intra-seasonal song variation in the Colombian Pacific humpback whale population, a unique and diverse breeding stock. We analyzed 37 h of recordings collected during two distinct periods of the 2019 breeding season (July and August–September) in the northern Colombian Pacific. Song repertoires were compared between periods, and the acoustic structure of a common song unit (Unit1) was analyzed using spectrographic cross-correlation. Results revealed a decrease in repertoire diversity over the course of the season, along with an increase in the song rate and the acoustic consistency of Unit1 during the second period. These findings highlight the dynamic nature of humpback whale song production and suggest potential influences of social learning and hormonal modulation. Such insights may be useful for the conservation and monitoring of humpback whale populations in breeding areas.